Biomarkers for characterization of heart failure – Distinction of heart failure with preserved and reduced ejection fraction. (15th January 2017) - Sinning, Christoph; Kempf, Tibor; Schwarzl, Michael; Lanfermann, Simon; Ojeda, Francisco; Schnabel, Renate B.; Zengin, Elvin; Wild, Philipp S.; Lackner, Karl-J.; Munzel, Thomas; Blankenberg, Stefan; Wollert, Kai C.; et al.
Abstract: Background: Heart failure (HF) incidence is rising worldwide and HF with preserved ejection fraction (HFpEF) represents nearly half of all cases. Treatment options are still limited in HFpEF in comparison to HF with reduced ejection fraction (HFrEF). Methods: We analyzed biomarkers in the general population to characterize HFpEF and HFrEF and defined a biomarker index to differentiate HFpEF from HFrEF. Growth differentiation factor-15 (GDF-15), soluble source of tumorigenicity 2 (sST2), C-reactive protein (CRP) and NT-proBNP were measured in 5000 individuals of the population-based Gutenberg Health Study (GHS). The median follow-up time for all-cause mortality was 7.3 years with 213 events. Results: Identification of subjects with HF was improved by GDF-15 (p < 0.001) in addition to NT-proBNP with an odds ratio (OR) of 1.4 (95% confidence interval [CI]:1.1–1.7). Discrimination of subjects with and without HF was slightly higher for GDF-15 (area under the ROC curve [AUC]:0.79 [95%CI:0.75–0.83]) compared to NT-proBNP (AUC:0.77 [95% CI:0.72–0.82]). For subjects with HF, differentiating HFpEF from HFrEF was feasible with the index ((CRP + GDF-15 + sST2)/NT-proBNP) with an OR of 3.7 (95% CI:1.9–8.5) (p < 0.001). The best biomarkers predicting all-cause mortality were NT-proBNP and GDF-15 with a hazard ratio (HR) of 1.9 (95% CI:1.6–2.2) and 1.7 (95%CI:1.6–1.9) (both p < 0.001), respectively. Conclusion: GDF-15 was useful to detect prevalent HF in addition to NT-proBNP and was elevated in HFrEF and HFpEF, whereas NT-proBNP was higher in HFrEF than in HFpEF. All biomarkers were useful to predict mortality in the general population. The index of ((CRP + GDF-15s + sST2)/NT-proBNP) was able to discriminate HFpEF from HFrEF.